Analisis Keberhasilan Implementasi Model Pembelajaran Discovery Learning dalam Pembelajaran Matematika Tingkat Perguruan Tinggi - Nur Fajrin Maulana Yusuf; Al Ikhlas; Unan Yusmaniar Oktiawati; Singgih Prastawa; Roni Chandra; Joni Wilson Sitopu (Departement of Mathematics Education, 2024)
This research aims to analyse the successful implementation of the discovery learning model in mathematics learning at the tertiary level. Discovery learning is one of the innovative learning models that encourages students to be actively involved in the learning process by discovering mathematical concepts by themselves. actively in the learning process by discovering mathematical concepts independently. independently. The research method used is a case study on a mathematics study programme in a university. study programme in a university. Data were collected through classroom observation, interviews with classroom observation, interviews with lecturers and students, and document analysis. The results The results showed that the implementation of discovery learning in mathematics learning in higher education is generally successful in improving students' conceptual understanding, critical thinking skills, and motivation to learn. learning. However, there are some challenges such as the lack of skills students' skills in independent learning, limited time allocation for learning, and lecturers' readiness in designing and managing discovery learning, and lecturers' readiness in designing and managing discovery learning. Research This research provides practical implications for lecturers and higher education institutions in developing and implementing discovery learning in developing and implementing an effective discovery learning model in mathematics courses. learning model in mathematics courses. Recommendations for future research is to explore student mentoring strategies and professional development of lecturers in the implementation of innovative learning models.